2022
DOI: 10.1109/access.2022.3203584
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Tomography Hardware Systems for Real-Time Applications: a Review

Abstract: This paper presents a review of two-dimensional (2D) and three-dimensional (3D) electrical tomography (ET) hardware accelerators for real-time applications. While many recent review papers have discussed various algorithms for image reconstruction or acquisition systems, none of them has considered state-of-the-art hardware implementations of the associated image reconstruction algorithms to achieve real-time performance, especially for 3D ET where the computation requirement is excessively high. A 3D ET is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…It can be observed that a general-purpose PC is widely used for the reconstruction of the image, with a few implementations utilizing FPGAs or external GPUs. A detailed review of some recent work for image reconstruction can be found in [11]. The reconstruction speed is directly dependent on the number of electrodes and mesh elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that a general-purpose PC is widely used for the reconstruction of the image, with a few implementations utilizing FPGAs or external GPUs. A detailed review of some recent work for image reconstruction can be found in [11]. The reconstruction speed is directly dependent on the number of electrodes and mesh elements.…”
Section: Resultsmentioning
confidence: 99%
“…The overall throughput of the EIT systems is defined by both the acquisition and the data processing (reconstruction) modules. While there have been multiple solutions to increasing the acquisition speeds, such as multi-frequency or partial measurements or improved hardware, the reconstruction has been mostly limited to utilizing general-purpose PC [11] with some standard library such as EIDORS [12] for carrying out the computation. The computation involves several matrixbased calculations in an iterative or non-iterative way for 2D image reconstruction.…”
Section: Image Reconstruction and Challengesmentioning
confidence: 99%
“…These include dedicated software built around multi-core processing as well as the expansion of statistical tools such as R to enable support for parallel processing. Most of these solutions limit themselves to the CPU, which at best contains tens of cores and hundreds of threads (43, 44). Modern GPUs on the other hand house over thousands to tens of thousands of cores on a single chip.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of highly conductive medium such as multi-phase flow featuring high water-cut and low gas void fraction (GVF) or in the case of brain/breathe monitoring, the ERT or EIT technique is preferred. An electrical current in the frequency range of a few kHz to up to 10 MHz is applied across two electrodes, and the voltage output across all the other electrodes is recorded and used for 2D or 3D image reconstruction [17]. Synchronous detection (i.e., phase-sensitive detection) is used to eliminate low-frequency drift components of the voltage signal.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, high spatial and temporal resolution ET systems are yet to be developed, despite the fact that they are highly desirable in several applications. The development of powerful edge processors based on GPU, FPGA, and/or multi-core CPUs will enable the rapid execution of iterative and complex tomography forward-inverse algorithms such as iterative Gauss-Newton, iterative Landweber, total variation, and even CNN/DNN algorithms in the near future [17]. This also requires high-speed acquisition solutions.…”
mentioning
confidence: 99%